Bright spots for advancing ecological understanding and conservation decision‐making - Holly S. Embke; Zachary S. Feiner; Gretchen J. A. Hansen; Daniel Isermann; Olaf P. Jensen; Christopher I. Rounds; Quinnlan C. Smith; M. Jake Vander Zanden (Conservation Biology, 2025)
A lot can be learned by studying bright spots—defined as unexpected positive outcomes. In fields like public health, education, and oncology, identifying factors behind bright spots reveals previously unknown drivers of success that can be replicated elsewhere. This concept is being applied in conservation but is hampered by variations in definitions of bright spots and confusion with hotspots—sites with high absolute values of a metric. We developed a framework to clearly define and distinguish between hotspots (e.g., a wetland with high plant diversity) and bright spots (e.g., a biodiverse wetland in a housing development), which outperform conservation expectations. The framework is an iterative cycle, consisting of setting expectations for relative comparisons, classifying systems into bright, dark, hot, and cold categories, and digging deeper to reveal hidden mechanisms and opportunities for intervention. We drew on examples from diverse fields to demonstrate how our framework can generate new knowledge, identify potential interventions, and inform management priorities. Defining conservation and management expectations, often through predictive models, is essential to understanding drivers of success and fosters hypotheses about overlooked factors. Our framework can enhance ecological understanding, guide interventions, and help prioritize actions in conservation and natural resource management.

Responses of larval fish and zooplankton to whole-lake 2,4-D herbicide treatments used to control Eurasian watermilfoil in northern Wisconsin lakes - Nicholas Rydell; Rebecca Gehri; Justin VanDeHey; Daniel Dembkowski; Kevin Gauthier; Scott Van Egeren; John Kubisiak; Michelle Nault; Daniel Isermann (Hydrobiologia, 2025)

Resist‐accept‐direct (RAD) considerations for climate change adaptation in fisheries: The Wisconsin experience - Zachary S. Feiner; Aaron D. Shultz; Greg G. Sass; Ashley Trudeau; Matthew G. Mitro; Colin J. Dassow; Alexander W. Latzka; Daniel A. Isermann; Bryan M. Maitland; Jared J. Homola; Holly S. Embke; Michael Preul (Fisheries Management and Ecology, 2022)
Decision‐makers in inland fisheries management must balance ecologically and socially palatable objectives for ecosystem services within financial or physical constraints. Climate change has transformed the potential range of ecosystem services available. The Resist‐Accept‐Direct (RAD) framework offers a foundation for responding to climate‐induced ecosystem modification; however, ecosystem trajectories and current practices must be understood to improve future decisions. Using Wisconsin's diverse inland fisheries as a case study, management strategies for recreational and subsistence fisheries in response to climate change were reviewed within the RAD framework. Current strategies largely focus on resist actions, while future strategies may need to shift toward accept or direct actions. A participatory adaptive management framework and co‐production of policies between state and tribal agencies could prioritise lakes for appropriate management action, with the goal of providing a landscape of diverse fishing opportunities. This knowledge co‐production represents a process of social learning requiring substantial investments of funding and time.

Resisting ecosystem transformation through an intensive whole‐lake fish removal experiment - Holly S. Embke; Stephen R. Carpenter; Daniel A. Isermann; Giancarlo Coppola; Douglas T. Beard; Abigail J. Lynch; Greg G. Sass; Zachary S. Feiner; M. Jake Vander Zanden (Fisheries Management and Ecology, 2022)
Lake ecosystems are shifting due to many drivers including climate change and landscape‐scale habitat disturbance, diminishing their potential to support some fisheries. Walleye Sander vitreus (Mitchill) populations, which support recreational and tribal fisheries across North America, have declined in some lakes. Climate change, harvest, invasive species and concurrent increases in warm‐water fishes (e.g. Centrarchidae) may have contributed to declines. To test the utility of an intensive management action to resist walleye loss, an experimental removal of ~285,000 centrarchids from a 33‐ha lake over 4 years was conducted while monitoring the fish community response. Centrarchid abundance declined and yellow perch Perca flavescens (Mitchill) increased, yet no evidence of walleye recruitment was observed. These findings explore the feasibility of intensive resistance as a management strategy in supporting walleye facing environmental change and provide a platform for management discussions to move beyond resist strategies in the Resist‐Accept‐Direct (RAD) framework to navigate ecosystem change.

Diets of double‐crested cormorants in the Lake Winnebago System, Wisconsin - Ryan P. Koenigs; Daniel J. Dembkowski; Charles D. Lovell; Daniel A. Isermann; Adam D. Nickel (Fisheries Management and Ecology, 2021)
Double‐crested cormorant Phalacrocorox auritus Lesson (cormorant) populations have increased throughout the Great Lakes region of North America causing concern related to the impact of cormorant predation on fish communities. A recent decline in yellow perch Perca flavescens (Mitchill) abundance within the Lake Winnebago System, Wisconsin, USA, prompted an assessment of cormorant diets to evaluate potential effects of cormorant predation on the sportfish community. Diets were collected from 883 cormorants (417 from Lake Winnebago and 466 from Lake Butte des Morts) between 2015 and 2017. Cormorant diets on both waterbodies consisted mostly of freshwater drum Aplodinotus grunniens Rafinesque and gizzard shad Dorosoma cepedianum (Lesueur). Yellow perch and walleye Sander vitreus (Mitchill) observations were infrequent and represented

Absence of PCB Hot Spot Effect in Walleye Sander vitreus from Lower Green Bay of Lake Michigan - Charles P. Madenjian; Daniel J. Dembkowski; Daniel A. Isermann; Stuart A. Batterman; Sergei M. Chernyak; Stewart F. Cogswell; Mark E. Holey (Archives of Environmental Contamination and Toxicology, 2019)

Defining a Safe Operating Space for inland recreational fisheries - Stephen R Carpenter; William A Brock; Gretchen J A Hansen; Jonathan F Hansen; Joseph M Hennessy; Daniel A Isermann; Eric J Pedersen; K Martin Perales; Andrew L Rypel; Greg G Sass; Tyler D Tunney; M Jake Vander Zanden (Fish and Fisheries, 2017)
The Safe Operating Space ( SOS ) of a recreational fishery is the multidimensional region defined by levels of harvest, angler effort, habitat, predation and other factors in which the fishery is sustainable into the future. SOS boundaries exhibit trade‐offs such that decreases in harvest can compensate to some degree for losses of habitat, increases in predation and increasing value of fishing time to anglers. Conversely, high levels of harvest can be sustained if habitat is intact, predation is low, and value of fishing effort is moderate. The SOS approach recognizes limits in several dimensions: at overly high levels of harvest, habitat loss, predation, or value of fishing effort, the stock falls to a low equilibrium biomass. Recreational fisheries managers can influence harvest and perhaps predation, but they must cope with trends that are beyond their control such as changes in climate, loss of aquatic habitat or social factors that affect the value of fishing effort for anglers. The SOS illustrates opportunities to manage harvest or predation to maintain quality fisheries in the presence of trends in climate, social preferences or other factors that are not manageable.